A literature review on the impact of work environment, leadership styles and resilience on job performance in UAE - Alkaabi, Maktoum Rashed Obaid Sultan; Kudus, Norliah; Ab Rahman, Zaizul (ResearchTrentz Academy Publishing Education Services, 2022)
This research reviewed literature related to the impact of work environment, leadership styles and resilence on job performance in UAE. In the curse of this review, it was figured out that, work environment tremendously affects the job performance of an employee in many ways, likewise leadership style. Both leadership style, work environment and resilience impacted on job performance in UAE based on the reviewed literature.